Pengendalian Cacat Produk Pisang Nugget di IKM Almauzu dengan Pendekatan Metode Six Sigma - Adlina Safitri Helmi; Indah Kurnia Ramadhani; Nessa Januarista (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2024)
Indonesia has an excellent program that is to develop industries upstream to downstream. IKM Almauzu is one of the downstream enterprises that processes agricultural products such as banana fruits some of its products are Banana nuggets, Babana roll, Banana Ball, Risoles and Fried Spring Roll but the main product is Banana Nugget. In one-week IKM Almauzu can produce 850 pcs or 142 boxes of Banana Nuggets. In the production process of Banana Nugget products, it is necessary to carry out quality improvements to minimize product defects. Quality control is carried out with a six-sigma approach that aims to minimize defects and is used as a benchmark for quality control. The study was carried out for one week and it was found that the types of defects are defects such as different thickness of the pod, uneven degree of maturity of the product and uneven baking of bread flour. With the implementation of this six-sigma method, it is hoped that the quality control of the production process at IKM Almauzu can